Experimental Analysis of Bending Stiffness Characteristics of Grouted Double Mortise-Tenon Joint for Prefabricated Metro Station Structure. (23rd June 2021) - Yang, Xiuren; Lin, Fang; Huang, Meiqun
Abstract : The grouted mortise-tenon joint, invented as the connection between the large prefabricated components, is the key to the prefabricated underground structures, and the double-tenon joint is most widely used in the prefabricated metro station structure. This paper conducts characteristic analysis of bending stiffness with a 1 : 1 prototype test in key working direction of different joint types for grouted double mortise-tenon joint. The results show that the double-tenon joint is characteristic of variable stiffness under different loads. Change laws of double-tenon joint bending stiffness without and with auxiliary pretightening device in tension side and compression side are also discussed. The correlations for calculating double-tenon joint bending stiffness with various axial loads and bending moments are derived at last, which offers the theory foreshadowing of similar joints.